Evolution of mortality during covid-19 pandemic in the first 120 days according to relevant indicators in 72 affected countries - Cieza Zevallos, Javier (2021)
Introduction: In late December 2019, China reported a group of pneumonia cases of unknown cause identified as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The pandemic generated by the SARS 2 virus, recognized by the WHO as COVID-19, is a relevant health phenomenon for all humanity. The objective is to analyze the course of mortality from the pandemic based on the most relevant characteristics of the countries with varying degrees of involvement 120 days after detecting their first case. Methodology: It is a longitudinal study of case series. The cases are affected countries in different magnitudes and followed daily from their first reported case until the day they had 120 days of evolution, considering the 1st day of observation is January 22, 2020. Results: Among the variables that show greatest effect size related to mortality are: Transmissible diseases, Poverty, TB Mortality and mortality related to non-transmissible diseases. By the day 120 the variables that maintain association are: Percentage of urban population, Men’s proportion, Obesity rate and percentage of Diabetic people. Conclusion: This pandemic invites us to focus on aspects related to the pathophysiology of the disease, especially those related to the behavior of the structure of man as a unit; but also to concepts about the distribution of wealth, the enormous economic imbalances.